Management of cluster development of agricultural enterprises in conditions of digitalization, legal risks, innovative education and smart economy - Gorobets, Nataliia; Горобець, Наталія Миколаївна; Verhun, Mykhailo; Вергун, Михайло; Nemashkalo, Karina; Немашкало, Каріна; Vovk, Volodymyr; Вовк, Володимир; Mazur, Nataliya; Мазур, Наталія; Brovarets, Oleksandr; Броварець, Олександр; et al. (Сільськогосподарська академія Університету Вітаутаса Великого, 2024)
The article examines the management of cluster development of agricultural enterprises in the conditions of digitalization, legal risks, innovative education and Smart economy. The need to implement digital technologies, automation and digital resource management, which contributes to increasing the productivity and competitiveness of agricultural enterprises, is substantiated. Legal risks associated with data protection and intellectual property management are considered, as well as the need to integrate innovative education to train specialists capable of working in the conditions of the Smart economy. It has been proven that the clustering of enterprises makes it possible to implement innovations more efficiently, optimize production processes and minimize costs, which contributes to the sustainable development of the agricultural sector. It is recognized that the use of the modified distribution method of the closed type allows to optimize the comparison of the forecasted volumes of production with the available actual resources of agricultural enterprises. In the conditions of growing digitalization, this approach contributes to increasing the efficiency of resource allocation due to more accurate accounting of actual indicators and forecasted needs. It was emphasized that the model of cluster development of agricultural enterprises in combination with new technologies, such as Smart economy, allows enterprises to join forces to increase competitiveness and optimize production processes. У статті досліджено управління кластерним розвитком аграрних підприємств в умовах цифровізації, правових ризиків, інноваційної освіти та розумної економіки. Обґрунтовано необхідність впровадження цифрових технологій, автоматизації та управління цифровими ресурсами, що сприяє підвищенню продуктивності та конкурентоспроможності сільськогосподарських підприємств. Розглянуто правові ризики, пов’язані із захистом даних та управлінням інтелектуальною власністю, а також необхідність інтеграції інноваційної освіти для підготовки спеціалістів, здатних працювати в умовах розумної економіки. Доведено, що кластеризація підприємств дає змогу ефективніше впроваджувати інновації, оптимізувати виробничі процеси та мінімізувати витрати, що сприяє сталому розвитку аграрного сектору. Визнано, що використання модифікованого методу розподілу закритого типу дозволяє оптимізувати порівняння прогнозованих обсягів виробництва з наявними фактичними ресурсами сільськогосподарських підприємств. В умовах зростаючої діджиталізації такий підхід сприяє підвищенню ефективності розподілу ресурсів за рахунок більш точного обліку фактичних показників і прогнозованих потреб. Було наголошено, що модель кластерного розвитку аграрних підприємств у поєднанні з новими технологіями, такими як Smart economy, дозволяє підприємствам об’єднати зусилля для підвищення конкурентоспроможності та оптимізації виробничих процесів.
Моделювання кластерного розвитку сільськогосподарських підприємств в умовах діджиталізації, правових ризиків, інноваційної освіти та смарт-економіки
Keywords: cluster development; кластерні розробки; smart economy; розумна економіка; agricultural enterprises; аграрні підприємства; management; менеджмент; digitalization; цифровізація; legal risks; правові ризики; innovative education; інноваційна освіта